2012
DOI: 10.1172/jci64240
|View full text |Cite
|
Sign up to set email alerts
|

T2R38 taste receptor polymorphisms underlie susceptibility to upper respiratory infection

Abstract: Innate and adaptive defense mechanisms protect the respiratory system from attack by microbes. Here, we present evidence that the bitter taste receptor T2R38 regulates the mucosal innate defense of the human upper airway. Utilizing immunofluorescent and live cell imaging techniques in polarized primary human sinonasal cells, we demonstrate that T2R38 is expressed in human upper respiratory epithelium and is activated in response to acyl-homoserine lactone quorum-sensing molecules secreted by Pseudomonas aerugi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

46
1,044
3
11

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 500 publications
(1,104 citation statements)
references
References 92 publications
46
1,044
3
11
Order By: Relevance
“…In contrast, on other mucosal surfaces, such as the urethral lining, these qualities represent potentially harmful (aversive) content. Bacteria produce and secrete bitter receptor-activating substances (5,37,38). In biofilms, such substances from the Gram-negative bacterium Pseudomonas aeruginosa, one of the predominant causative microorganisms in catheter-associated urinary tract infection (39), can reach concentrations as high as 600 μM (40).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, on other mucosal surfaces, such as the urethral lining, these qualities represent potentially harmful (aversive) content. Bacteria produce and secrete bitter receptor-activating substances (5,37,38). In biofilms, such substances from the Gram-negative bacterium Pseudomonas aeruginosa, one of the predominant causative microorganisms in catheter-associated urinary tract infection (39), can reach concentrations as high as 600 μM (40).…”
Section: Discussionmentioning
confidence: 99%
“…Taste Compounds-All analyzed compounds have been described previously in the literature as bitter tasting (100 -105) or as representing small molecules responsible for cell-tocell communications that have been conjectured to activate bitter taste receptors outside of the oral cavity (55,106). Bitter chemicals were purchased mainly from Sigma-Aldrich, Fluka (Oberhaching, Germany), ABCR (Karlsruhe, Germany), ICN Biochemicals (Aurora, USA), BioChemica (Darmstadt, Germany), ChromaDex (LGC Standard, Wesel, Germany), CPS ChemieϩService GmbH (Aachen, Germany), Cfm Oskar Tropitzsch (Marktredwitz, Germany), Carl Roth (Karlsruhe, Germany), and HWI Analytik (Rülzheim, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Our experiments revealed that mouse Tas2r105, as well as human TAS2R1, TAS2R10, and TAS2R14, is sensitive to various N-acyl homoserine lactones. We failed, however, to monitor N-acyl homoserine lactone responses for TAS2R38 (55), which may be explained by the use of different experimental methodologies. The ability to detect quorum-sensing molecules contributes to environmental adaptions and influences the behavior of eukaryotic organisms (84,85).…”
Section: Substancementioning
confidence: 97%
See 2 more Smart Citations